The Genetic Methylation Testing: Assessing Important Genes MTHFR, MTRR, MTR, AHCY, and COMT - Ahmed, Rashed; Tamim, MD.TANZIMUR RAHMAN (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Genetic methylation testing is a valuable method for understanding the complex biochemical processes of methylation, a core cellular function influencing gene expression, detoxification, neurotransmitter balance, and overall metabolic health. This study is interested in assessing five critical genes — MTHFR, MTRR, MTR, AHCY, and COMT — that regulate the methylation cycle and influence important physiological functions. Mutations in these genes can disrupt methylation processes and result in numerous health disorders, including cardiovascular disease, neurological diseases, and detoxification dysfunction.Through a literature review and mixed-methodology study, this research determines the individual functions of each gene in methylation. The MTHFR gene is crucial in the metabolism of folate to its active form, and its mutations link to elevated levels of homocysteine, which have cardiovascular implications. The MTR and MTRR genes regulate homocysteine to methionine conversion, and polymorphisms in them may result in metabolic disruptions. The AHCY gene regulates the breakdown of S-adenosylhomocysteine for efficient donation of methyl groups, and COMT plays a crucial role in catecholamine metabolism affecting mood and stress.The study calls attention to the clinical relevance of these genetic mutations, requiring tailored treatments such as tailored supplementation with methylated B vitamins, diet modification, and precision medicine interventions. Significant barriers are the complexity of gene-environment interactions and the need for standardization procedures for interpretation of genetic data. Future trends include extension of genetic screening with more extensive gene panels and integration of methylation insights into the art of medicine for more patient-specific care.